Maternal effects and Symbiodinium community composition drive differential patterns in juvenile survival in the coral Acropora tenuis. Issue 10 (October 2016) - Quigley, Kate M.; Willis, Bette L.; Bay, Line K.
Abstract : Coral endosymbionts in the dinoflagellate genus Symbiodinium are known to impact host physiology and have led to the evolution of reef-building, but less is known about how symbiotic communities in early life-history stages and their interactions with host parental identity shape the structure of coral communities on reefs. Differentiating the roles of environmental and biological factors driving variation in population demographic processes, particularly larval settlement, early juvenile survival and the onset of symbiosis is key to understanding how coral communities are structured and to predicting how they are likely to respond to climate change. We show that maternal effects (that here include genetic and/or effects related to the maternal environment) can explain nearly 24% of variation in larval settlement success and 5–17% of variation in juvenile survival in an experimental study of the reef-building scleractinian coral, Acropora tenuis . After 25 days on the reef, Symbiodinium communities associated with juvenile corals differed significantly between high mortality and low mortality families based on estimates of taxonomic richness, composition and relative abundance of taxa. Our results highlight that maternal and familial effects significantly explain variation in juvenile survival and symbiont communities in a broadcast-spawning coral, with Symbiodinium type A3 possibly a critical symbiotic partner during this early life stage.